Sykes-Picot Treaty and Its Effects on the Division of Tigris and Euphrates River Basin on Kurdistan - تالیب, جه‌زا تۆفیق; علاءالدین, عطا محمد (Sulaimani Journal for Humanities, 2018)
ABSTRACT Sykes-Picot Treaty and Its Effects on the Division of Tigris and Euphrates River Basin on Kurdistan Currently, the issue of water is one of the most perilous matters which need an accurate and precise study. one of the effects of the sykes-picot treaty in 1916 is the emergence of this issue between the countries which partook the tigris and euphrates basin, regarding that a huge part of the basin is located in kurdistan, the basin was divided among turkey, syria, iraq, and iraq, so the kurdish people has been divided among them as well. From this point of view, directly or indirectly Kurdish people are involved in the issues of the aforementioned countries, and the division of the profit of water was one of the prominent issues in the area. thus, this study is dedicated to discuss the state of both the tigris and euphrates rivers basin concerning the division and distribution of the basin and its annual profits, and highlighting the agreements that are particularly hold upon the arrangement of the division of water among the countries partaking the basin, as well as discussing the dreadful effects of the treaty upon the population of the abovementioned countries in general and especially the kurds, which the results are of huge disadvantageous regarding the political, national, social and economical issues to the kurdish nation.